Private Toll Roads: A Dynamic Equilibrium Analysis - Robin Lindsey; André de Palma (Tinbergen Institute, 1997)
In recent years there has been a surge of interest in private toll roads as an alternative to public free-access road infrastructure. Private toll roads have gained favour for a variety of reasons, including theirpotential to alleviate traffic congestion, shrinking public funds for road construction and maintenance,and growing acceptance of the user-pay principle.This paper takes the profitability of private toll roads as given, and focuses on their allocativeefficiency. The model features one origin and one destination linked by two parallel routes that candiffer in capacity and free-flow travel time. Congestion takes the form of queueing. Individuals decidewhether to drive, and if so on which route and at what time. Three private ownership regimes areconsidered: a private road on one route and free access on the other route, competing private roads, anda mixed duopoly with a private road competing with a public toll road. The efficiency gain (measuredby social surplus) in each regime is measured relative to the efficiency gain derived from applying first-best optimal tolls on both routes.Private toll roads are generally found to enhance efficiency. The efficiency gain is greater when tollsare varied over time to eliminate queueing, when competing routes are also tolled, when no private roadhas a dominant fraction of total capacity, and when a private road does not suffer a significant traveltime disadvantage. Paradoxically, a mixed duopoly can be less efficient than a private duopoly. Priceleadership by a public toll road operator avoids this possibility, although leadership typically yieldslittle efficiency gain.
Keywords: 330; private toll roads; bottleneck congestion; departure time; second-best pricing; Straßenbaufinanzierung; Lastmanagement; Theorie